Circulating lipocalin 2 is associated with body fat distribution at baseline but is not an independent predictor of insulin resistance: the prospective Cyprus Metabolism Study - Liu, Xiamen; Hamnvik, Ole-Petter R.; Petrou, Michael; Gong, Huizhi; Chamberland, John P.; Kales, Stefanos N.; Christiani, David C.; Mantzoros, Christos S.; Christophi, Costas A. (My University, 2011)
Objective: Lipocalin 2 (LCN2 or NGAL), a protein derived from neutrophils, macrophages, adipocytes, and other cells, has been proposed to be a link between obesity and insulin resistance (IR), but animal and cross-sectional human studies have revealed conflicting results. We studied the association of serum lipocalin 2 with anthropometric, metabolic, and cardiovascular risk markers in young healthy men cross-sectionally and, for the first time, prospectively after 2 years of follow-up, with and without adjustment for potential confounders including serum creatinine. Design: Two hundred and seventy-two participants were randomly selected from the Cyprus Metabolism Study (1056 men, 18 years), of whom 93 subjects participated in the follow-up study 2 years after baseline assessment. Associations were also explored between total and free leptin levels (to serve as positive controls) and anthropometric metabolic variables. Results: In the cross-sectional study, lipocalin 2 levels were marginally correlated in the unadjusted model with central fat distribution but not with body weight or total body fat mass. After adjusting for age, smoking, activity, body mass index, fat percentage, waist-to-hip ratio, and serum creatinine, no correlation was found with any cardiovascular risk factor. There was no correlation with the homeostasis model assessment of IR (HOMA-IR) at baseline. In the prospective analyses, baseline levels of lipocalin 2 were not predictive of any variables in unadjusted or adjusted models. As expected, total and free leptin were associated with anthropometric and metabolic variables both cross-sectionally and prospectively. Conclusions: We demonstrate that lipocalin 2 is not an independent predictor of metabolic and cardiovascular risk factors in young men cross-sectionally or prospectively.
Keywords: Section of Endocrinology; Lipocalins; Gelatinases; Neutrophil gelatinase-associated